Impact of forest fires on water quality and nutrient dynamics in burned streams in Patagonia - Brand, Cecilia (2025)
Wildfires affect extensive areas worldwide each year, causing profound impacts. Their effects on water quality vary depending on soil characteristics, hydrologic regimes, and fire severity. In March 2021, a large wildfire affected over 13,000 ha of Patagonian Forest in Argentina. To assess its impact on water quality, four streams draining burned catchments and four reference streams were selected. Fire-related effects were observed in conductivity, total suspended solids (TSS), and nutrients. Conductivity and TSS peaked initially at 144.5 mg/l (1.7× than reference sites) and 30.5 mg/l (22.1×), respectively. Study-wide trends indicate a sustained enrichment of nitrogen forms in burned sites and a decline in phosphorus levels. Initial total phosphorus (TP)concentrations reached 112.5 μg/l (17×). The highest total nitrogen (TN) value was observed at last high-flow sampling in burned sites (845.6 μg/l, 10.4×), mainly driven by an increase in NO₃− + NO₂− . TN export overall study average was 325.8 kg/km2/yr (11×), while TP export reached its maximum at the first high-flow period. Most metal concentrations exhibited similar trends in burned and reference streams, peaking after the first postfire rainfall, with significantly higher levels of arsenic in burned sites. These findings underscore the significant and lasting impacts of wildfires on aquatic ecosystems, highlighting the need for management strategies that mitigate the consequences of such extreme events on freshwater biodiversity and ecosystem functioning. Post-fire conditions require a focused assessment due to potential synergistic impacts on water quality.